THE COMPLETE GROUP OF FUNDAMENTAL CONSTANTS OF PHYSICS - Kuzmenkov, Serhii (Physical and Mathematical Education, 2022)
Formulation of the problem. The article discusses the problem of completeness of the group of fundamental constants of physics. The analysis of the existing lists of different authors made it possible to conclude that none of them solves the problem. Different authors justify different lists due to the lack of 1) clear criteria for the fundamentality of constants and 2) consensus regarding the concept of the completeness of the group of fundamental constants. Therefore, the study of this problem is relevant. Materials and methods. The conducted research was based on the works of such authors as Y.L. Rosenthal (1984), P. Davis (1982/1985), L.B. Okun (1991), K.A. Tomilin (2006), O.P. Spiridonov (2015) and was carried out through systematization, comparative analysis, theoretical understanding of scientific publications and educational literature, generalization and clarification of ideas of scientists. The results. 1. In our opinion, a group of constants can be considered complete if its members are necessary and sufficient for a complete description of our Universe. 2. The introduction of the cosmological constant Λ as a constant characterizing the dark energy that dominates our Universe is justified to the group of dimensional constants. 3. The introduction of the principle of correspondence between groups of dimensional and dimensionless fundamental constants, which would make it possible to unambiguously move from one group to another, is substantiated. 4. According to the principle of correspondence to the group of dimensionless fundamental constants, a dimensionless cosmological constant was introduced. 5. The consistent application of the correspondence principle made it possible to clarify and supplement the group of dimensionless constants, in particular, to add two constants and , with which the dimensional constants c (speed of light) and ħ (Planck’s constant) can be matched. 6. In order to ensure complete correspondence between the groups of dimensional and dimensionless constants regarding weak and strong interaction, the introduction of the Fermi constant and the value of the color charge gqg to the group of dimensional constants is justified. 7. The meaning of the dimensionless Hubble constant has been clarified (Kuzmenkov, 2022). Conclusions. So, we have formed two complete (to date) groups of fundamental constants of physics (dimensional and dimensionless) with 12 members in each and a system of equations that unambiguously describe the transition from one group of constants to another.